ANALISIS DAN PERANCANGAN SISTEM INFORMASI SIMPAN PINJAM PADA KOPERASI PEGAWAI NEGERI IAIN SULTAN THAHA SAIFUDDIN JAMBI - Dui Astuti; Joni Devitra (Jurnal Manajemen Sistem Informasi, 2017)
Cooperative civil servants IAIN Sultan Thaha Saifuddin Jambi is a Cooperative composed of civilservants who take shelter in the environs of the Jambi, STS IAIN in practice more prioritizing businessSave borrowed. But businesses save borrow managed KPN has not been equipped with an integratedinformation system. The use of technology in the processing of the data Save borrowed that still rely onapplication program Microsoft Word and Excel resulting in multiple various obstacles faced by businessin KPN, such as: frequent occurrence of inconsistencies and redundancies in the data, as well as thelength of the search process and data access/information. For it is needed a web-based information systemthat integrates and can overcome the problems in the field of loan save on KPN IAIN Sultan ThahaSaifuddin mosque Jambi, both in terms of data processing, distribution of information to members and allinterested parties, as well as in terms of search and access data/information. Information systems saveloan at KPN is designed by using the PHP programming language and uses structured modelingtechniques in the form of DFD and ERD to reflect the results of the analysis and design of the system.The output of this research is to design a prototype information system save loan on a Cooperative civilservants IAIN Sultan Thaha Saifuddin Jambi. Expected by the existing information systems save borrowthis can contribute to the improvement of information systems save loan which runs at KPN IAIN STSJambi.